1986
DOI: 10.1590/s0006-87051986000100014
|View full text |Cite
|
Sign up to set email alerts
|

Densidade básica do colmo e sua correlação com os valores de brix e pol em cana-de-açúcar

Abstract: Neste estudo procurou-se estabelecer as correlações entre a densidade básica do colmo e os valores de Brix e Pol em diversas variedades e "seedlings" de cana-de-açucar, visando ao estabelecimento de um método expedito e semiquantitativo de análise. Os resultados obtidos mostraram correlações significativas (p > 99%) entre a densidade básica do colmo e os valores obtidos para Brix e Pol, principalmente para a região mediana do colmo. Desse modo, a densidade básica do colmo pode ser utilizada como um método e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
0
1
1
Order By: Relevance
“…The MID values found in this study were notably higher than the 1.05-1.58 g cm −3 reported in the literature (Azzini et al, 1986;Klein, 2010), indicating that the varieties showed higher accumulations of sucrose, especially varieties RB 863129 and RB 98710 at 483 days. This variable, according to Azzini et al (1986) and Fernandes (2000), is positively correlated with Brix and Pol, which indirectly determine the concentration of sucrose (Oliveira et al, 2012). Therefore, stalk density is a variable that can predict the concentration of sucrose in the plant in a simple and economic manner.…”
Section: Discussioncontrasting
confidence: 75%
“…The MID values found in this study were notably higher than the 1.05-1.58 g cm −3 reported in the literature (Azzini et al, 1986;Klein, 2010), indicating that the varieties showed higher accumulations of sucrose, especially varieties RB 863129 and RB 98710 at 483 days. This variable, according to Azzini et al (1986) and Fernandes (2000), is positively correlated with Brix and Pol, which indirectly determine the concentration of sucrose (Oliveira et al, 2012). Therefore, stalk density is a variable that can predict the concentration of sucrose in the plant in a simple and economic manner.…”
Section: Discussioncontrasting
confidence: 75%
“…Segundo Silva et al (2008), as variedades que apresentaram maior produção de matéria natural por hectare, foram aquelas que também apresentaram elevada porcentagem de colmo. Azzini et al, (1986) apresentaram correlações positivas e altamente significativas entre a densidade básica na região média do colmo (g/cm 3 ) e os valores de CS (BRIX e POL). Ainda naquele estudo, se demonstrou a relevância dessas relações funcionais para a indústria açucareira, devido ao fato de se encontrar também associadas à concentração de sacarose na planta por conta do elevado peso específico dessa molécula em comparação aos demais componentes da fração solúvel do caldo.…”
Section: Discussionunclassified